Evaluation of inactivated infectious bovine rhinotracheitis vaccines. - Schipper, I A (1975)
Sixty-five calves of approximately three months of age and of mixed sex were vaccinated twice at four week intervals with either attenuated or inactivated infectious bovine rhinotracheitis vaccines. Following initial vaccination there was no demonstrable serum infectious bovine rhinotracheitis titer in any of the calves receiving the inactivated vaccine with 20.7% of the calves receiving the attenuated vaccines having demonstrable titers. Following a second administration of vaccine at eight weeks post-initial vaccination 63.9% of the calves receiving the inactivated vaccine had no demonstrable titer with 72.4% of the calves receiving the attenuated vaccine exhibiting a blood titer of four or greater.